Research on River Health Assessment of Hanjiang River Basin - ZHANG Yajuan; ZHAO Xiaochen; CHEN Jipei (Renmin Zhujiang)
Health assessment of rivers and lakes is an important means of their health management.To meet the requirements of ecological civilization construction and river chief system in the new circumstances,this paper performs the classified assessment and comprehensive evaluation of the Hanjiang River Basin from five aspects:hydrological integrity,morphological and structural integrity,chemical integrity,biological integrity,and the sustainability of social service function according to the relevant methods in the Technical Guidelines for River and Lake Health Assessment (SL/T 793—2020).The assessment results show that the Hanjiang River Basin is in a state of health overall,and the score of the main stream of the Hanjiang River is slightly higher than that of its tributaries.The hydrological integrity and biological integrity of the sub-criterion layer are weak,which leads to the ecological conditions in a state ranging from sub-health to health.The social service function of the sub-criterion layer is sustainable,and the functional status is in the state of health.The health assessment of rivers and lakes in the Hanjiang River Basin is of great significance to promote its water resources protection and water environment management and ensure the sustainable utilization of its water resources.